2015
DOI: 10.1007/s13277-015-4648-8
|View full text |Cite
|
Sign up to set email alerts
|

PTEN and p16 genes as epigenetic biomarkers in oral squamous cell carcinoma (OSCC): a study on south Indian population

Abstract: Phosphatase and tensin homolog (PTEN) and p16INK4a (p16) genes are tumor suppressor genes, associated with epigenetic alterations. PTEN and p16 promoter hypermethylation is a major epigenetic silencing mechanism leading to cancer. The cooperation between PTEN and p16 in pathogenesis of cancers suggest that their combination might be considered as potential molecular marker for specific subgroups of patients. Hence, the present study aimed to investigate whether PTEN and p16 promoter methylations were involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In this study, 72.5% of OSCC have well differentiated grade, whereas moderately and poorly differentiated OSCC grade (III) constituted 17.5% and 10%, respectively. As reported in other studies, the majority of the patients presented with well or moderately differentiated tumors, most frequently located in the mobile tongue, floor of mouth and alveolar rim 35 . Alshawi (2010) 24 studied OSCC grading and revealed likewise percentages to our results (71.42% in grade I, 17.14% in grade II and 11.41 % in grade III).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, 72.5% of OSCC have well differentiated grade, whereas moderately and poorly differentiated OSCC grade (III) constituted 17.5% and 10%, respectively. As reported in other studies, the majority of the patients presented with well or moderately differentiated tumors, most frequently located in the mobile tongue, floor of mouth and alveolar rim 35 . Alshawi (2010) 24 studied OSCC grading and revealed likewise percentages to our results (71.42% in grade I, 17.14% in grade II and 11.41 % in grade III).…”
Section: Discussionsupporting
confidence: 78%
“…The p16 INK4A gene is located on chromosome 9p21, and as a tumor suppressor gene, playing a key role in cell cycle regulation. It codes for a protein which binds and inhibits cyclin-dependent kinases (CdK-4and -6) 35 . It also inhibits phosphorylation of Rb and promotes the formation of an Rb-E2F repressive transcriptional complex, so as to blocks the progression of cell cycle at the G1-S point.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 1 μg genomic DNA was modified with bisulfite using a CpGenome DNA modification kit (Chemicon, Temecula, CA, USA). The modified DNA was amplified with primers for the methylated and unmethylated gene sequences designed according previously published reports (Table S1) . The reactions were carried out using the Veriti 96‐well thermal cycler (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…The modified DNA was amplified with primers for the methylated and unmethylated gene sequences designed according previously published reports (Table S1). (25)(26)(27)(28) The reactions were carried out using the Veriti 96-well thermal cycler (Applied Biosystems). Polymerase chain reaction conditions are listed in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the authors suggested that epigenetic changes in these genes might represent a valuable biomarker for the early detection of OSCC. 59 Similarly, the expression of γ-synuclein (SNCG) is related to the development of various carcinomas, including OSCC (Table 1). In their study, Cheng et al examined a correlation between DNA methylation in the SNCG gene and the development of OSCC, including the clinical symptoms of this malignancy.…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 99%